Association of CYP2C19, CYP3A5 and GPIIb/IIIa gene polymorphisms with Aspirin and Clopidogrel Resistance in a cohort of Indian patients with Coronary Artery Disease. (12th August 2015) - Arya, V.; Mahajan, P.; Saraf, A.; Mohanty, A.; Sawhney, J. P. S.; Bhargava, M.
Summary: Introduction: Dual antiplatelet therapy with clopidogrel and aspirin is the current standard of care in the management of patients with coronary artery disease (CAD) and acute coronary syndrome (ACS). The variability in response to these antiplatelet agents may be due to the underlying genetic diversity. This study was designed to determine the resistance to aspirin and clopidogrel in Indian patients and to look for correlation, if any, with selected polymorphisms. Methods: Platelet function testing by light transmission aggregometry was performed on 72 patients with CAD/ACS who were stable on dual antiplatelet therapy (clopidogrel 75 mg OD and aspirin 150 mg OD) along with 72 controls. Aspirin resistance was considered as mean platelet aggregation ≥70% with 10 μ m ADP and ≥20% with 0.75 mm arachidonic acid. Clopidogrel resistance was defined as <10% decrease from the baseline in platelet aggregation in response to ADP 10 μ m and semi‐response as <30% decrease from the baseline. Polymorphisms CYP2C19*2, *3, CYP3A5*3 and PLA1/A2 were genotyped. Results: We found 51.4% patients with inadequate response to clopidogrel (1.4% resistant and 50% semi‐responders) and 5.5% patients semi‐responders to aspirin, none being completely resistant. The genotype and allele frequencies of CYP2C19*2 and PLA1/A2 gene polymorphisms were significantly different between clopidogrel semi‐responders and responders. Carriers of CYP2C19*2 and CYP3A5*3 showed diminished inhibition of platelet aggregation. No significant correlation was found between coronary events, type of coronary intervention with clopidogrel nonresponsiveness. Conclusion: Unlike aspirin, a high proportion of partial responders to clopidogrel were identified. In an interim analysis on 72 Indian patients, a significant association was found between CYP2C19*2 and PLA1/A2 in clopidogrel semi‐responders.